Políticas culturais no Ceará: as ações de interiorização da SECULT (2003-2006) - Lopes, Paulo Rodrigo Soares (2018)
This research aims to understand the actions for the purpose of interiorizing and decentralizing promoted by the Culture Department from Ceará, between 2003 and 2006. For this purpose, it is taken as the subject of analyses the “Culture in Movement: SECULT Itinerant” programme which has crossed the state of Ceará, during a year, to spread its policies and actions. The program execution demanded a face-to-face among SECULT and town halls and city councils. It was considering this dynamic that it was proposed the central concerns of this paper which, besides the search to understand the motives from intern of cultural management of state, on what concerns the implementation of a new image-brand, this research also understand which dynamics the program “Culture in Movement: SECULT Itinerant” imputed new relations among SECULT and politics and cultural field. To reconstruct the forces in was necessary: (1) bibliographic survey about the themes interesting to that paper; (2) the categorization and analysis of interviews given by the agents from the cultural management and from political field in brochures; (3) survey and analysis of newspapers, aiming to structure the relationship between SECULT and culture field; and (4) the execution of interviews with individuals how have taken part of the management at the time. As result, the text, here presented, says that the “interiorization” it was the brand of SECULT, in the period between 2003-2006. Two aspects were highlighted: a) the changing of symbolic from modernization to cearensidade; and b) Claudia Leitão's nomination. The cearensidade oriented the SECULT practices. That perspective got strength in the context of federal management, where MinC promoted a dimension called Brazilian cultural diversity.